RETURN ON ASSET AND EARNING PER SHARE ON STOCK PRICES IN CONSUMER GOODS INDUSTRY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN THE PERIOD 2021-2023 - Sari, Laynita; Herlina, Zelvi Fitria; Septiano, Renil (Bina Bangsa International Journal of Business and Management, 2025)
Study this aiming for know influence Return On Asset and Earning Per Share against price shares in the company sector Consumer Goods Industry. Population study this is 109 companies and samples as many as 66 companies with amount of data obtained as many as 198 were determined with use method purposive sampling. As for source data used is secondary data. This data sourced from Report Annual Report and Financial Statements in companies sector Consumer Goods Industry listed on the Indonesia Stock Exchange. Research this use technique data analysis with method panel data regression for test connection between variables studied. And with other tests such as model fit tests (CEM, FEM, REM), Chow test, Haussman test, assumption test classical, hypothesis testing, and multiple linear regression testing. The results of the study this explain that return on assets has an effect positive and significant to price shares, earning per share no influential to price share.